Pacote de Umbraco para configurar conteúdo para um cliente móvel - Lacerda, Tiago Rafael Pinto (2024)
This thesis aims to address the demand of digitalization by developing a package capable of being installed in any Umbraco project that will allow users to create and customise their desired mobile app. That structure is then extracted in such a way that a code generator is able to create a cross-platform mobile solution that will give developers a jump start to customize the solution according to more specific needs, trying to achieve not only the replication of the existing functionalities in the website, but also to introduce specific features that take advantage of components available exclusively on mobile devices. This initiative responds to client demands for rapid mobile app development from existing Umbraco websites, while also aiming to enrich the Umbraco community with enhanced functionalities. The systematic mapping review conducted aimed to consolidate comprehensive knowledge of Umbraco, content management systems, packages, and elements of code generation. A proof of concept was successfully developed, compatible with any Umbraco website version 12 or higher. This package enables users to customize mobile applications directly within the Umbraco backoffice interface, facilitating generation with minimal effort. Agap2IT supports continuous integration pipelines, enabling ongoing mobile app generation. The initial goal was to develop both the package and the code generator within this project. However, because of the approaching deadlines and the effect on our submission for the Umbraco Awards, the company decided to form a team of two developers. One developer would handle the code generator, while I would be responsible for creating and distributing the Umbraco package, which will be the primary focus of this thesis. This project has the potential to make cross-platform mobile app development more accessible, empowering users with no specialized programming skills to leverage the familiar Umbraco Backoffice environment for app creation.